Conceptualisation as basis for the development ofcritical thinking within the nursing perspective - Pretoruis, Louise; Van Dyk, Agenes; Small, Luis; Amukugo, Hans Justus (International Journal of Advanced Nursing Studies, 2016)
The purpose of this article is to present the conceptualise empirical findings arrived at from the needs assessment (phase 1), which reflected the application of critical thinking skills by the respondents. The ultimate aim was to develop an educational programme to facilitate critical thinking in nursing practice. Conceptualization as the definition of key concepts in a study with a view to integrating one’s research into conceptual frameworks.The findings revealed six main concepts and their related sub-concepts. These concepts included interpretation, analysis, evaluation, inference, explanation and self-regulation. These concepts were inferred from the deduction by the researcher. These concepts were the results of the concept analysis of critical thinking by 46 experts directed by Facione together with the related dispositions. These six main concepts constituted the framework within which the educational programme was developed. The following steps were followed during the conceptualization namely concepts synthesis, clarification of the concepts, interpretation of the concepts, analysis of the concepts, evaluation of the concepts, interference/ conclusion, explanation, self – regulation and critical approaches.